International Scientific Conference Energy Management of Municipal Transportation Facilities and Transport EMMFT 2017 (Advances in Intelligent Systems and Computing,, 2018)
This book includes the proceedings of the 19th International Scientific Conference "Energy Management of Municipal Transportation Facilities and Transport EMMFT 2017", which was held in Khabarovsk, Russia on 10-13 April 2017. The book presents the research findings of scientists working at universities in the Far Eastern, Siberian and Ural Federal Districts of Russia, and of Serbia, which are unique regions notable for sustainably operating complex transport infrastructures in severe climatic and geographic environments. It also offers practical insights into transportation operation under such conditions. The book discusses the experiences of colleagues from Slovenia, Ukraine and Latvia in the development of transport infrastructure and construction of transport facilities and features and includes the results of a wide range of studies, such as managing multimodal transportation, improving the efficiency of locomotives, electric locomotives, traction substations, electrical substations, relay protection and automation devices, and power-factor correction units. It addresses topics like renewable energy sources, problems of the mathematical and simulation modelling of electromagnetic processes of electrical power objects and systems, aspects of cost reduction for fuel-and-power resources, theoretical aspects of energy management, development of transport infrastructure, modern organizational and technological solutions in construction, new approaches in the field of management, analysis and monitoring in transport sector. Comprising 142 high-quality articles covering a wide range of topics, these proceedings are of interest to anyone engaged in transport engineering, electric power systems, energy management, construction and operation of transport infrastructure buildings and facilities.